Disowning the Mystery: Stump's Non-Apophatic Aquinas. Issue 1 (2nd January 2020) - Hewitt, Simon
ABSTRACT: On the face of it Aquinas stands in the mainstream of Western mystical theology, and in particular is a noteworthy proponent of negative theology. This view, however, is challenged within anglophone philosophical theology. The clearest attack on the view that Aquinas is an apophatic theologian is to be found in Eleonore Stump's Aquinas . This paper lays out Stump's reasons for reading Aquinas as non-apophatic, and shows that they are not convincing. Aquinas, it concludes, meant what he said when he claimed that we do not know what God is.